Ginsenoside F1 Promotes Cytotoxic Activity of NK Cells via Insulin-Like Growth Factor-1-Dependent Mechanism - Kwon, Hyung-Joon; Lee, Heejae; Choi, Go-Eun; Kwon, Soon Jae; Song, Ah Young; Kim, So Jeong; Choi, Woo Seon; Hwang, Sang-Hyun; Kim, Sun Chang; Kim, Hun Sik (Frontiers in Immunology, 2018)
Ginsenosides are the principal active components of ginseng and are considered attractive candidates for combination cancer therapy because they can kill tumors and have favorable safety profiles. However, the overall benefit of ginsenosides remains unclear, particularly in cancer immunosurveillance, considering the controversial results showing repression or promotion of immune responses. Here we identify a potentiating role of ginsenoside F1 (G-F1) in cancer surveillance by natural killer (NK) cells. Among 15 different ginsenosides, G-F1 most potently enhanced NK cell cytotoxicity in response to diverse activating receptors and cancer cells. G-F1 also improved cancer surveillance in mouse models of lymphoma clearance and metastatic melanoma that rely on NK cell activity. G-F1-treated NK cells exhibited elevated cytotoxic potential such as upregulation of cytotoxic mediators and of activation signals upon stimulation. NK cell potentiation by G-F1 was antagonized by insulin-like growth factor (IGF)-1 blockade and recapitulated by IGF-1 treatment, suggesting the involvement of IGF-1. Thus, our results suggest that G-F1 enhances NK cell function and may have chemotherapeutic potential in NK cell-based immunotherapy. We anticipate our results to be a starting point for further comprehensive studies of ginsenosides in the immune cells mediating cancer surveillance and the development of putative therapeutics.